Menguji Pertimbangan Mens Rea dalam Pemidanaan Kasus Korupsi - Arif Awaludin (Faculty of Law, Universitas Wijayakusuma, 2019)
The implementation of the mens rea element in cases of corruption in Indonesia is not uniform. Some law enforcers use it for proof, others don't use it. The concept of mens rea adopted from the common law legal system is still causing debate. Research that uses normative methods and refers to literature studies and studies of court decisions concluded that the application of the mens rea element is not always used by law enforcers. The development of the principle of error becomes the principle of no errors affecting decision making in every corruption case. Clarity of the elements of mens rea is needed in the law to create uniformity among law enforcers.Keyword: Mens Rea, Criminalization, Corruption